Evidence that flocking behavior is rewarded by singing, flock mates, and mu opioid receptors in the nucleus accumbens - Alyse N. Maksimoski; Taviah A. Levenson; Changjiu Zhao; Lauren V. Riters (PLoS ONE, 2025)
It has been proposed that social groups are maintained both by reward resulting from positive social interactions and by the reduction of a negative state that would otherwise be caused by social separation. European starlings, Sturnus vulgaris, develop strong conditioned place preferences for places associated with the production of song in flocks outside the breeding season (gregarious song) and singers are motivated to rejoin the flock following removal. This indicates that the act of singing in flocks is associated with a positive affective state and raises the possibility that reward induced by song in flocks may play a role in flock maintenance. The goal of this study was to begin to test this hypothesis. We found that birds that sang full songs developed stronger conditioned place preferences than non-singing birds for places associated with flock mates, indicating that singers find the presence of flock mates to be rewarding. Regardless of song rate, the presence of flock mates also induced analgesia (a reflection of the reduction of a negative state). This form of analgesia has been shown to be an indirect measure of opioid release, suggesting that the presence of flock mates may induce opioid-mediated reward. Consistent with this possibility, the numbers of mu opioid receptor immunolabeled cells in the nucleus accumbens correlated positively with measurements of gregarious song and other social behaviors. Results suggest that both gregarious song and social contact promote flock cohesion and that opioids released onto mu opioid receptors in the nucleus accumbens may play an important role.